IMPACT OF ENTREPRENEURIAL SELF EFFICACY ON ENTREPRENEURIAL INTENTION IN PT KARYA LENCANA MAS - Ika Puspa Satrianny; Thamrin Thamrin (Bajang Institute, 2022)
Entrepreneurial self-efficacy refers to a person’s belief in their ability to successfully achieve the tasks of entrepreneurship. Self-efficacy has been found to contribute significantly to performance. It will determine the level of motivation and effort exerted as well as how long entrepreneurs will persevere that is factors which may be factor for entrepreneurial success. The purpose of this research is to know whether there is the impact of entrepreneurial selfefficacy on entrepreneurial intention at PT Karya Lencana Mas. Research design used in this research is descriptive research design and correlational research design. Research methods which used are descriptive statistic analysis, validity and reliability test, normality test, coefficient correlation, coefficient of determinant, simple linear regression analysis and Z testing. The conclusion of this research is entrepreneurial selfefficacy has impact on entrepreneurial intention at PT Karya Lencana Mas.